SWOT Analysis As A Strategy To Improve Competitiveness In SEFOPE (State Secretariat Of Professional And Employee Training Training) In Timor-Leste (Case Study: In The Special HRD Part "Delivery Of Workers To South Korea 2015-2018 - Dircia dos Santos Ricardo; Hermien Tridayanti (Journal of World Conference (JWC), 2020)
This study aims to analyze and evaluate using the SWOT Analysis Technique as a Strategy to Increase Competitiveness at SEFOPE (State Secretariat for Employment Professional Training Affairs) in Timor-Leste (Case Study: Part of the Special HRD "Delivery of Workers to South Korea 2015-2018"). This research is descriptive qualitative research. Population and sample researchers used the sampling method, respondents will be taken in this study, namely 6 important officials from the Top Manger Level employees of all employees. Data collection techniques used: Observation, documentation, interviews and questionnaires. In calculating the score used is a Likert scale with the provision of rating values and weights. The analysis used is: IFAS and EFAS techniques. The results of this study indicate that from the results of the research conducted, the SEFOPE Institution is in quadrant III namely the Defend quadrant which is also referred to as the WT strategy that uses weaknesses to overcome all existing threats.